El clero secular de Cuenca (Ecuador): actitudes ante la muerte (1651-1705) - Viforcos Marinas, María Isabel; Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 2001)
It is an approximation to the attitudes toward death observed by a group of clergymans from Cuenca (Ecuador) during the second half of the XVII century. The wills of this social elite show us not only a snapshot of the economic situation but also the opportunity of approaching their beliefs, affections and values revealing a moral determined, to a large extent, by the social formalism and conventionality.